MANAGEMENT ACCOUNTING PRACTICES AND PERFORMANCE ON MSMES IN INDONESIA - Eni Kaharti (Universitas Veteran Bangun Nusantara, 2023)
This study was designed to examine the effect of Management Accounting Practices (MAP) on the performance of Micro, Small, and Medium Enterprises (MSMEs) in the Kebumen Region of Central Java in Indonesia. Methods: A survey research design approach was used using a structured questionnaire to collect data from 140 MSME owners. Data were analyzed using descriptive and inferential statistical tools using SPSS version 20. Result: PAM does not affect the performance of MSMEs, except for Strategic Management when it is partially tested. PAM affects the performance of MSMEs when tested simultaneously. The results show a strong positive relationship between the dependent variable (company performance) and the independent variable (Cost Determining System, Budgeting System, Performance Evaluation System, Decision Support System, and Strategic Management Accounting System). Implication: This study recommends that SMEs make more use of contemporary MAP to ensure profitability and business sustainability.